A COMPARATIVE STUDY ON THE IMPACT OF COVID PANDEMIC PARANOID ON INVESTMENT BEHAVIOUR OF BANKING AND NON BANKING PROFESSIONALS IN INDIA - Sendilvelu, Kannadas; Parthasarathy, Srikanth (Indian Journal of Finance and Banking, 2022)
The study focuses on comparing the investment behaviour of banking and non-banking professionals in India and also, how the Covid pandemic has impacted their behaviour towards investments as such. The aim of the project is to understand if there are any differences in the investment choices of both sets of people. For the purpose of the study, data has been collected from banking and non-banking employees through the issue of google forms, and the same data has been used to analyse the behaviours among the targeted groups. A sample of 122 data points is considered for the study, with banking and non-banking professional samples. The questions try to bring out the actual behaviour of the respondents with regards to their investments, before and after the Covid pandemic. With that, comparison of banking and non-banking, in particular, will be well understood by the reader of the study. Apart from that, statistical models like Chi-square test, Regression analysis and Correlation analysis have been done for the collected set of data points. By the end of the study, the gain is all about the idea and understanding about the investment behaviour of the banking and non-banking employees that the Covid pandemic has made any impact on the investment behaviour of people. JEL Classification Codes: G4, G11, G40, G41.